A dimensional approach to determine common and specific neurofunctional markers for depression and social anxiety during emotional face processing. Issue 2 (6th November 2017) - Luo, Lizhu; Becker, Benjamin; Zheng, Xiaoxiao; Zhao, Zhiying; Xu, Xiaolei; Zhou, Feng; Wang, Jiaojian; Kou, Juan; Dai, Jing; Kendrick, Keith M.
Abstract: Major depression disorder (MDD) and anxiety disorder are both prevalent and debilitating. High rates of comorbidity between MDD and social anxiety disorder (SAD) suggest common pathological pathways, including aberrant neural processing of interpersonal signals. In patient populations, the determination of common and distinct neurofunctional markers of MDD and SAD is often hampered by confounding factors, such as generally elevated anxiety levels and disorder‐specific brain structural alterations. This study employed a dimensional disorder approach to map neurofunctional markers associated with levels of depression and social anxiety symptoms in a cohort of 91 healthy subjects using an emotional face processing paradigm. Examining linear associations between levels of depression and social anxiety, while controlling for trait anxiety revealed that both were associated with exaggerated dorsal striatal reactivity to fearful and sad expression faces respectively. Exploratory analysis revealed that depression scores were positively correlated with dorsal striatal functional connectivity during processing of fearful faces, whereas those of social anxiety showed a negative association during processing of sad faces. No linear relationships between levels of depression and social anxiety were observed during a facial‐identity matching task or with brain structure. Together, the present findings indicate that dorsal striatal neurofunctional alterations might underlie aberrant interpersonal processing associated with both increased levels of depression and social anxiety.